Sexually transmitted coinfections among at-risk HIV-positive MSM: implications for optimal preemptive treatment - Wu, Tzong-Yow; Lin, Kuan-Yin; Su, Li-Hsin; Sun, Hsin-Yun; Huang, Yu-Shan; Liu, Wang-Da; Liu, Wen-Chun; Chang, Lan-Hsin; Chang, Sui-Yuan; Hung, Chien-Ching (Frontiers in Medicine, 2024)
Background Concurrent sexually transmitted infections (STIs) are common in sexually active populations. We aimed to estimate the prevalence and coinfection rates of bacterial STIs among sexually active, HIV-positive men who have sex with men (MSM), and to assess the potential benefits of different combination treatment regimens in managing concurrent bacterial STIs. Methods From September 2021 to September 2023, HIV-positive MSM underwent STI testing when they had symptoms suggestive of STIs or recently acquired hepatitis C virus (HCV) infection or early syphilis. The oral rinse, rectal swab, and urethral swab specimens were tested for Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma spp., Ureaplasma spp., and Trichomonas vaginalis with the use of multiplex real-time polymerase-chain-reaction assays. The estimated coinfection rates were used to evaluate the benefits of different combination treatment regimens for managing coinfections. Results During the study period, 535 participants (median age, 37 years; and CD4 count, 615 cells/mm3) were enrolled. On their first visits, at least one bacterial pathogen was detected in 57.9% and concomitant bacterial infections were found in 32.9% of the participants. The most commonly identified pathogen was U. urealyticum (36.3%), followed by C. trachomatis (22.8%), and N. gonorrhoeae (19.8%). The factors associated with any bacterial STIs included older age (per 1-year increase, adjusted odds ratio [AOR], 0.97; 95% confidence interval [CI], 0.95–1.00), early syphilis (AOR, 1.87; 95% CI, 1.22–2.84), and having more than 5 sex partners in the preceding 3 months (AOR, 2.08, 95% CI, 1.07–4.06). A combination therapy of benzathine penicillin G with a 7-day course of doxycycline could simultaneously treat 27.1% of C. trachomatis coinfections in participants with early syphilis, while a combination therapy of ceftriaxone with doxycycline could simultaneously treat 40.6% of chlamydial coinfections in participants with gonorrhea. Conclusion Bacterial STIs were prevalent and concomitant infections were not uncommon among sexually active, HIV-positive MSM, supporting regular screening for bacterial STIs. The effectiveness of preemptive use of doxycycline as combination therapy for concurrent STIs warrants more investigations.